Psychological features of teenagers socialization in social and cultural context of postmodernism - Tokareva, Natalia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
he article is dedicated to the salient trends of teenagers’ socialization as a prerequisite for personal experience internalization in terms of radical transformations of the modern society. There are defined social and cultural concepts of postmodernism age that determine the need to rethink vectors of personal constructive development of a human-being while they are getting adult. The article states polymodality, variability, fragmentation behaviour of a teenager of the Information Society An empirical component of the research defines a content fullness of the indicators which are relevant to personal construct subsystems of the teenage students in the semantics of the behavioural strategies field. Personal constructs are learnt as integrative characteristics; they actualize the potential of an individual to operate successfully in a situation when they are uncertain. The features of psychological and pedagogical support of socialization for a modern teenager by means of communication examples are defined.